Alloreactive regulatory T cells generated with retinoic acid prevent skin allograft rejection. - Moore, C; Tejon, G; Fuentes, C; Hidalgo, Y; Bono, MR; Maldonado, P; Fernandez, R; Wood, K; Fierro, J; Rosemblatt, M; Sauma, D; Bushell, A (Wiley-VCH, 2015)
CD4(+) CD25(+) Foxp3(+) regulatory T (Treg) cells mediate immunological self-tolerance and suppress immune responses. Retinoic acid (RA), a natural metabolite of vitamin A, has been reported to enhance the differentiation of Treg cells in the presence of TGF-β. In this study, we show that the co-culture of naive T cells from C57BL/6 mice with allogeneic antigen-presenting cells (APCs) from BALB/c mice in the presence of TGF-β, RA, and IL-2 resulted in a striking enrichment of Foxp3(+) T cells. These RA in vitro-induced regulatory T (RA-iTreg) cells did not secrete Th1-, Th2-, or Th17-related cytokines, showed a nonbiased homing potential, and expressed several cell surface molecules related to Treg-cell suppressive potential. Accordingly, these RA-iTreg cells suppressed T-cell proliferation and inhibited cytokine production by T cells in in vitro assays. Moreover, following adoptive transfer, RA-iTreg cells maintained Foxp3 expression and their suppressive capacity. Finally, RA-iTreg cells showed alloantigen-specific immunosuppressive capacity in a skin allograft model in immunodeficient mice. Altogether, these data indicate that functional and stable allogeneic-specific Treg cells may be generated using TGF-β, RA, and IL-2. Thus, RA-iTreg cells may have a potential use in the development of more effective cellular therapies in clinical transplantation.